Pharmacognostic, antiplasmodial and antipyretic evaluation of the aqueous extract of Vernonia amygdalina leaf - Adiukwu, Paul Chukwuemeka; Agaba, Amon; Nambatya, Grace (International Journal of Biological and Chemical Sciences, 2011)
The impeding safety challenges to the use of herbs have made qualitative and quantitative evaluation of herbal preparations a necessity. This study was aimed at evaluating the pharmacognostic and pharmacological properties of V. amygdalina leaf. Methods used include standard procedure for macroscopic and microscopic examinations; ash and extractive values determination; and quantitative evaluation of phytochemicals of the leaf aqueous extract. 4-day antiplasmodial suppression test using mice and antipyretic evaluation in rats induced pyrexia by i.p administration of 15% w/v Saccharomyces cerevisiae were carried out. Data showed presence of calcium oxalates and animocytic stomata. Extractive values suggest high aqueous soluble constituents. Saponin at 9.18% w/w } 0.19, among the phytochemicals evaluated was highest. Ash values: total ash 11.33% w/w } 0.15 and acid insoluble ash 1.89% w/w } 0.19, were obtained. Parasite suppression on day 4 and dose induced body temperature decrease, were significant (P . 0.05) for all the 3 dose levels of the extract used. Study agrees with folkloric use of the leaf extract in malaria fever but suggests substantial antipyretic property of the leaf.
Keywords: Ash and extractive values, parasite suppression, temperature decrease.